2019
DOI: 10.4193/rhin19.158
|View full text |Cite
|
Sign up to set email alerts
|

The GALEN rhinosinusitis cohort: chronic rhinosinusitis with nasal polyps affects health-related quality of life

Abstract: Background: Chronic rhinosinusitis (CRS) significantly affects health-related quality of life (HRQoL). Few multinational observational studies have evaluated the impact of CRS with nasal polyps (CRSwNP) on patients' HRQoL. This study aimed to assess HRQoL outcomes (including analyses by disease severity and impact of comorbidities and refractory disease) in CRSwNP patients from a large European database. Methodology: Data were analysed from the Global Allergy and Asthma European Network (GALEN) Rhinosinusitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 35 publications
1
96
0
1
Order By: Relevance
“…2 A recent large single-center study from the United States reported that approximately 18% of patients with CRS have CRSwNP. 3 CRSwNP is associated with adult-onset asthma, significant morbidity, decreased health-related quality of life (HRQoL), [4][5][6][7][8] and substantial economic burden (amounting to more than $22 billion for CRS in the United States in 2014). 9,10 Quality of life (QoL) impairment is comparable with that experienced by patients with chronic lower back pain.…”
mentioning
confidence: 99%
“…2 A recent large single-center study from the United States reported that approximately 18% of patients with CRS have CRSwNP. 3 CRSwNP is associated with adult-onset asthma, significant morbidity, decreased health-related quality of life (HRQoL), [4][5][6][7][8] and substantial economic burden (amounting to more than $22 billion for CRS in the United States in 2014). 9,10 Quality of life (QoL) impairment is comparable with that experienced by patients with chronic lower back pain.…”
mentioning
confidence: 99%
“…1,26,31 NSAID-ERD in particular is thought to place an especially high clinical burden on affected patients. 9,34 The frequent recurrence of nasal polyps after surgery and a requirement for high-dose SCS to manage asthma, if present, reflect the persistent and aggressive nature of the disease. 42 In the USA, it is estimated that patients with CRSwNP with NSAID-ERD undergo an average of three sinus operations during their lifetime.…”
Section: Clinical Burdenmentioning
confidence: 99%
“…The disease burden with significantly lower physical and mental HRQoL than population norms is particularly high in CRSwNP. This is particularly in patients with comorbid asthma and/or NSAID-ERD 9 and in patients who need repeated treatment with corticosteroids and/or sinonasal surgeries to alleviate its uncontrolled symptoms. The impact on HRQoL is comparable with other chronic diseases such as chronic obstructive pulmonary disease (COPD), asthma, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Despite welldescribed differences between CRSwNP and CRSsNP, understanding the distinction between these 2 populations of CRS patients remains a timely and active area of investigation with therapeutic implications. 16,17 Patient perception of the CRS disease process is an increasingly recognized as an important modulator of the CRS disease course, affecting tolerance of symptoms and QOL impact felt by patients. [18][19][20][21][22] Patient perception of disease has not yet been well distinguished between CRSwNP and CRSsNP.…”
Section: Introductionmentioning
confidence: 99%
“…14 , 15 Despite well-described differences between CRSwNP and CRSsNP, understanding the distinction between these 2 populations of CRS patients remains a timely and active area of investigation with therapeutic implications. 16 , 17…”
Section: Introductionmentioning
confidence: 99%